"High" Motivation for Alcohol: What are the Practical Effects of Energy Drinks on Alcohol Priming?. (5th November 2012) - Peacock, Amy; Bruno, Raimondo
<x xml:space="preserve">Abstract</x> Background While several researchers have proposed a causal relationship between alcohol mixed with energy drink (AmED) consumption and subsequent alcohol intake, there is a dearth of research exploring the potential mechanisms underpinning this association. Methods Marczinski and colleagues (in press) report the results of a double‐blind, placebo‐controlled, between‐groups study assessing whether an initial AmED dose primes an increased motivation to drink relative to alcohol alone. Participants (n = 80) received either alcohol (0.91 ml/kg vodka), energy drink (ED; 1.82 ml/kg Red Bull®), AmED, or a placebo beverage and then self‐reported their motivation to drink via the Desire‐for‐Drug scale. Results Subjective ratings of "desire more alcohol" were significantly higher than predrink in the placebo, alcohol, and AmED conditions, with this effect apparent at more time points in the AmED condition. While it was concluded that EDs may increase alcohol priming, between‐condition analyses revealed that ratings did not differ significantly in AmED and alcohol conditions, with moderate magnitude treatment effects at most, and ratings of desire generally closer to 0 (absence of desire) than 100 (very much desire). Conclusions While the study by Marczinski and colleagues fills an important gap in the literature, direct measurement of AmED priming's effect on subsequent alcohol consumption using a within‐subjects design and appropriate statistical comparison is required to (i) establish the practical implications of these results for AmED consumers and (ii) discount any individual differences in such priming effects.